Amber Brown Sees Red - Danziger, Paula, 1944-; Ross, Tony (New York : Putnam's, 1997)
The year that she is in the fourth grade is a difficult one for Amber, as she tries to deal with escalating telephone fights between her divorced parents and her father's impending return to take joint custody of her.
Keywords: Divorce -- Fiction; Schools -- Fiction